Mesoporous Silica Nanoparticles for Bio-Applications - Niculescu, Violeta-Carolina (Frontiers in Materials, 2020)
Mesoporous materials with high specific surface, pores volume and unique pore size were recently intensively studied as bio-materials, such as carriers for controlled bio-active principles delivery. Mesoporous silica materials exhibit greater capacity for drugs loading and insure a controlled bio-active compound release if they are functionalized, in comparison with amorphous colloidal silica. Mesoporous silica nanomaterials have lately earned increasing interest also due to their substantial capability to be used in tumours treatment and imaging. Recently, functionalized mesoporous silica materials known a rapid development in imagistic and curative applications. This review summarizes the recent advancement in the obtaining and biological properties of mesoporous silica nanomaterials, emphasising the synthesis methods and drug delivery application. Commonly used synthetic strategies are discussed, followed by a systematic review of applicability in optical and MRI imaging.